PANGeA: PHYSICAL ACTIVITY AND NUTRITION FOR GREAT AGEING - Rado Pišot; Nika Pegan; Boštjan Šimunič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
The global problem of ageing is one of the most significant issues of modern society. With this issue arise the challenges of searching for healthy ageing criteria, which will enable individuals to enjoy a high quality of life and be independent in their old age. Research has already shown that the process and consequences of ageing have a strong correlation with lifestyle, but the criteria according to which ageing can be seen as healthy have not yet been defined. The Institute of Kinesiology Research of the Science and Research Centre of the University of Primorska decided to explore and study ageing criteria together with local and foreign partners in the Cross-border Cooperation Programme Slovenia - Italy 2007-2013 PANGeA: Physical Activity and Nutrition for Great Ageing. The project partners are now in the process of preparing the measurements for the study of the situation of the older population in the project area. By interpreting the characteristics of healthy and active elderly people, we will try to define the criteria of healthy ageing. The knowledge will then be applied in practice working with target groups with the cooperation of public institutions from participating regions that are active in the field of assuring the quality of life for the older population.